Women are more vulnerable to non-communicable diseases in rural and urban Bangladesh (P18-082-19) - Mridha, Malay; Hasan, Mehedi; Khan, Showkat; Hossain, Mokbul; Sutradhar, Ipsita (Oxford Academic, 2022)
This article was published in the Current Developments in Nutrition [Copyright © American Society for Nutrition 2019. This article is published and distributed under the terms of the Oxford University Press, Standard Journals Publication Model (https://academic.oup.com/journals/pages/open_access/funder_policies/chorus/standard_publication_model)] and the definite version is available at: https://doi.org/10.1093/cdn/nzz039.P18-082-19 The Journal's website is at: https://academic.oup.com/cdn/article/3/Supplement_1/nzz039.P18-082-19/5517793?login=true